High yield growth of vertically aligned carbon nanostructure through low frequency induced plasma enhanced chemical vapour deposition. (30th August 2019) - Xu, Cigang; Cooke, Mike
Abstract: A novel plasma process for the high yield synthesis of vertically aligned carbon nanostructure has been studied, with the plasma generated from low frequency (LF, 50–460 kHz), either LF alone or its combination with high frequency (RF, 13.56 MHz). The growth properties are investigated as a function of power level and frequency of LF plasma, and the power level of plasma generated from the combination of LF and RF. It was found that the diameter, growth rate and areal density of carbon nanostructure depends on the plasma conditions. A novel pulsed plasma operation mode has been developed to alleviate the etching effect of plasma and prepare carbon nanostructure with higher growth rate and higher density, and the corresponding mechanism has been proposed. The approach to tune ion bombardment for beneficial effect on the growth of novel materials can be employed by other plasma processes.